El despertar del padre : escritura e infancia en Domingo Faustino Sarmiento - Alejandra Josiowicz (Cuadernos LIRICO)
This essay analyzes the figure of the death of the child in La vida de Dominguito, by Domingo Faustino Sarmiento, in a double sense : on the one hand, in its relationship with language, as an event that symbolizes the coming to the word and, on the other, as a trauma that establishes a fundamental discontinuity in the father’s experience. It examines the emergence of childhood at three different levels : first, the child as remembered through autobiographical writing ; second, the child’s written word as incorporated to the text ; and last, the death of the child as a traumatic experience in its irreducible otherness. It concludes that such scene poses an ethical necessity to which the text seeks to respond.